Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Mechanochemistry in Materials 2017
DOI: 10.1039/9781782623885-00001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry: Inspiration from Biology

Abstract: Mechanochemistry refers to the study of the evolution of the formation and disruption of chemical bonds upon application of an external force. In this chapter, the roles of mechanical forces in different biological systems are highlighted along with mechanisms and mechanotransduction pathways showing how complex biological systems can provide inspiration for materials design. Examples of how mechano-based systems have been mimicked by other scientists are also discussed including self-healing systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Several review articles and books have comprehensively summarized the advancements in various types of mechanoresponsive polymeric materials and mechanochemical polymer synthesis. 18–24 However, on-going efforts continue to inspire significant progress in this field. We firmly believe that the future direction lies in the development of novel mechanochemically responsive polymeric materials, as well as exploring their advantageous applications in toughening materials through force-triggered ring-opening reactions, free radical reactions, and click reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Several review articles and books have comprehensively summarized the advancements in various types of mechanoresponsive polymeric materials and mechanochemical polymer synthesis. 18–24 However, on-going efforts continue to inspire significant progress in this field. We firmly believe that the future direction lies in the development of novel mechanochemically responsive polymeric materials, as well as exploring their advantageous applications in toughening materials through force-triggered ring-opening reactions, free radical reactions, and click reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers can be engineered to exhibit responses to a diverse variety of external stimuli including changes in temperature, 1–5 light, 6–9 pH, 10–12 magnetic fields, 13–16 electric fields, 17–19 ultrasonication, 20,21 mechanical forces, 22,23 and many others. 24–28 Arguably, thermoresponsive behavior of polymers is studied most extensively in these stimuli-responsive materials space.…”
Section: Introductionmentioning
confidence: 99%
“…Among the many sought-after responses, we are interested in (i) controlling polymer degradation, especially within the context of cradle-to-grave or cradle-to-cradle strategies, and (ii) adjusting the modulus of the material on command. 9 The ability to transform the mechanical properties of a material, or mechanomorphism, 10 also constitutes a desirable feature. For instance, Gossweiler et al demonstrated the mechanical activation of covalent bonds in polymers with repeatable shape recovery, 11 while Fox et al developed a bioinspired, water-enhanced mechanical gradient nanocomposite.…”
Section: Introductionmentioning
confidence: 99%